1990
DOI: 10.2307/3869259
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Endogenous and Foreign Genes in Chloroplast Transformants of Chlamydomonas

Abstract: Transcription from modified chloroplast genes has been studied in vitro, but only with the recently developed ability to stably introduce foreign DNA into Chlamydomonas reinhardtii chloroplast chromosomes in situ has it become possible to do so in vivo. Cloned chloroplast DNA sequences, into which had been inserted chimeric genes composed of the GUS coding sequence reporter under transcriptional control of chloroplast promoters for the C. reinhardtii atpA, atpB, and rbcL genes, were introduced into the cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 19 publications
(23 reference statements)
3
51
0
Order By: Relevance
“…In each set of protection experiments in which we used low amounts of total RNAs from the two strains (<2.5 u,g), we observed that protection of the rbcL probe was considerably higher than that of the afpA probe. This indicated that rbcL transcripts were particularly abundant in the two strains, an observation that is consistent with the much higher transcription rate for rbcL than for afpA or afpB genes (Blowers et al, 1990).…”
Section: Characterization Of the Transcript Destabilization By The Ncsupporting
confidence: 73%
See 1 more Smart Citation
“…In each set of protection experiments in which we used low amounts of total RNAs from the two strains (<2.5 u,g), we observed that protection of the rbcL probe was considerably higher than that of the afpA probe. This indicated that rbcL transcripts were particularly abundant in the two strains, an observation that is consistent with the much higher transcription rate for rbcL than for afpA or afpB genes (Blowers et al, 1990).…”
Section: Characterization Of the Transcript Destabilization By The Ncsupporting
confidence: 73%
“…Our pulse labeling studies indicated that the a subunit was synthesized in large excess over the p subunit. This cannot be accounted for by differences in transcript availability as both the rates of transcription and steadystate levels of the transcripts are similar for the two genes (Blowers et al, 1990;Leu et al, 1990). Therefore, this difference in the rates of protein synthesis rather points to a regulation at the translational level.…”
Section: The Destabilization Of the Atpa Transcript In Mutant Nccl Almentioning
confidence: 99%
“…These strains contained a chimeric petD promoter/5Ј UTR-uidA (␤-glucuronidase) coding region-rbcL 3Ј UTR reporter gene, which was located downstream of and in opposite orientation to the endogenous atpB gene. This insertion site has been used for numerous uidA gene fusions in the past (10,11,19) and does not affect the expression of atpB, which is used as the selectable marker for transformation of the nonphotosynthetic recipient strain CC373 (see "Experimental Procedures").…”
Section: Resultsmentioning
confidence: 99%
“…2 were based on pDG2 (19). This plasmid contains the petD promoter and 5Ј UTR translationally fused to the uidA coding region and rbcL 3Ј UTR, and the chimeric gene is inserted into the large inverted repeat of the chloroplast genome downstream of the atpB gene (11). We previously engineered a BglII site into the petD 5Ј UTR at position ϩ25 relative to the mature RNA 5Ј end, which lengthens the transcript by 6 nt and is present in pDG2 (19).…”
Section: Gene Constructions and Transformationsmentioning
confidence: 99%
See 1 more Smart Citation